A composite indicator analysis for optimizing entrepreneurial ecosystems - Lafuente, Esteban; Ács, Zoltán J.; Szerb, László (Research policy, 2022)
•We use the ‘benefit of the doubt’ (BOD) weighting to evaluate the entrepreneurial ecosystem at the global scale.•We compute endogenous weights to identify country-specific policy priorities.•We show how countries can design optimal entrepreneurship policy using objective criteria.•Effective policy is conditional on the configuration of countries’ entrepreneurial ecosystem.•Quality improvements in entrepreneurial ecosystems are conducive to higher levels of venture capital investments. We employ the ‘benefit of the doubt’ approach rooted in non-parametric techniques to evaluate the entrepreneurial ecosystem of 71 countries for the period 2016. By scrutinizing the relative efficiency of countries’ entrepreneurial ecosystems, the proposed analysis of composite indicators allows the computation of endogenous (country-specific) weights that can be used for developing more informed policy making. The results show that countries prioritize different aspects of their national system of entrepreneurship which confirms that, contrary to homogeneous prescription, tailor-made policy is necessary if the objective is to optimize the resources deployed to enhance the countries’ entrepreneurial ecosystem. The findings of the empirical application reveal significant improvements in the quality of the entrepreneurial ecosystem can be realized by targeting the policy priorities of the local entrepreneurship system identified by the ‘benefit of the doubt’ weights. By analyzing the variation in economic and entrepreneurship outcomes over the seven-year period centered on the study year (period 2013–2019), we found a significant positive correlation between quality improvements in the entrepreneurial ecosystem and venture capital investments.